TOTAL PHENOLIC CONTENT, ANTIOXIDANT CAPACITY AND STARCH HYDROLYTIC ENZYME INHIBITION OF THE EXTRACTS FROM UNPOLISHED COLORED RICES - Dao, Le Hoang; Hung, Pham Van (Vietnam Journal of Biotechnology, 2018)
The different colors of rice are contributed by various phenolic compounds, which have various health benefits. However, phenolic compounds, which are mostly existed in rice bran and easily lost during milling. Therefore, the consumption of unpolished rice is recommended to prevent from many diseases. The objective of this study is to determine total phenolic and flavonoid contents, antioxidant capacity and diabetic enzyme inhibition potential of the extracts of the different unpolished colored rices. Three kinds of unpolished colored rices (unpolished white rice, unpolished red rice and unpolished black rice) grown in Vietnam were used to extract their bioactive compounds by alcoholic solvent extracting method. The results showed that the highest level of total phenolic content (TPC) was found in unpolished red rice (470.96 µg FAE/g db sample), while the lowest was in unpolished white rice (135.84 µg FAE/g db sample). TPC of rice in free form was considerably higher than that in the bound form. Total flavonoid content in free form was also significantly higher than bound form. Total flavonoid content in free form of unpolished black rice (126.75 µg RE/g db sample) was higher than that in the others. In the present study, unpolished red rice extract possessed the best antioxidant activity (78.79%) in most cases, and showed the strongest inhibitory potential against alpha-amylase (78.56%) and amyloglucosidase (36.13%) as well. As a result, extracts of unpolished colored rices could act like both antioxidant and enzyme inhibitors and have a potential to be used in prevention of type 2 diabetes